Three Reasons for Hospitality: Care for Others, Care for the World, and Care of the Self. Issue 1 (24th March 2022) - Taylor, Abigail; Lefebvre, Alexandre
Abstract : We seek to answer a deceptively simple question: why do private citizens in liberal democracies offer hospitality to undocumented migrants? Through qualitative interviews with French citizens, we propose three reasons. The first is widely recognized in the scholarly literature: hospitality is offered out of a care and concern for vulnerable and precarious migrants. However, we uncover two additional reasons that are not acknowledged in studies on hospitality. One is the desire by citizens to uphold the basic principles and ideals of their own society (what we call "care for the world"). Another is the desire on the part of citizens themselves to become a different and better kind of person by practicing hospitality (what we call "care of the self"). We provide a multifaceted account of what motivates citizens to offer hospitality even in situations where it is outlawed by their own governments.